Lower Extremity Surgical Treatment to Improve Function in a Patient with Gollop-Wolfgang Complex: A Case Report. Issue 2 (April 2019) - Albright, Patrick; Veenstra, Joshua; Habeck, Jason; Bovid, Karen
Abstract : Case: Gollop-Wolfgang Complex (GWC) includes congenital absence of the tibia with ipsilateral distal femur bifurcation associated with hand/foot ectrodactyly. A 20-month-old male presented with GWC, including left bifid distal femur with ipsilateral tibial hemimelia and absent extensor mechanism, hypoplastic bilateral thumbs, and right foot tarsal-type preaxial polydactyly. Left through-knee amputation preserving growth and contralateral polydactyly reconstruction were performed. Complications of wound infection and dehiscence were successfully treated. Patient is 44 months old and ambulating with left knee disarticulation prosthesis and right supramalleolar orthosis. Conclusions: Through-knee amputation and prosthetic fitting provides limb function for GWC patients with tibial hemimelia lacking an extensor mechanism.